2016
DOI: 10.18632/oncotarget.7927
|View full text |Cite
|
Sign up to set email alerts
|

Oroxylin A modulates mitochondrial function and apoptosis in human colon cancer cells by inducing mitochondrial translocation of wild-type p53

Abstract: Oroxylin A is a flavonoid extracted from the root of Scutellaria baicalensis Georgi. We previously demonstrated that oroxylin A induced apoptosis in human colon cancer cells via the mitochondrial pathway. In the present study, we investigated the underlying mechanisms responsible for the mitochondrial apoptotic pathway triggered by oroxylin A. p53 regulates mitochondrial survival, mitochondrial DNA integrity, and protection from oxidative stress. We determined that oroxylin A induces p53 mitochondrial transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Cancer cells can be severely starved from nutrients and oxygen in an ischemic tumor microenvironment due to poor tumor vascularization (Gorrini et al, 2013; Trachootham et al, 2009), making cancer an excellent model to study nutrient regulation of redox homeostasis in mammals. As reported previously (Qiao et al, 2016; Semenza, 2000), deprivation of nutrients and oxygen, an ischemic condition, leads to rapid inhibition of mTORC1 signaling as shown by the decreased phosphorylation of mTORC1 effectors S6K1 and S6, but activation of AMPK and HIF1α, two hypoxic markers (Figure 6A). Similarly to the yeast results, human SOD1 but not SOD2 becomes rapidly activated (Figure 6A).…”
Section: Resultssupporting
confidence: 82%
“…Cancer cells can be severely starved from nutrients and oxygen in an ischemic tumor microenvironment due to poor tumor vascularization (Gorrini et al, 2013; Trachootham et al, 2009), making cancer an excellent model to study nutrient regulation of redox homeostasis in mammals. As reported previously (Qiao et al, 2016; Semenza, 2000), deprivation of nutrients and oxygen, an ischemic condition, leads to rapid inhibition of mTORC1 signaling as shown by the decreased phosphorylation of mTORC1 effectors S6K1 and S6, but activation of AMPK and HIF1α, two hypoxic markers (Figure 6A). Similarly to the yeast results, human SOD1 but not SOD2 becomes rapidly activated (Figure 6A).…”
Section: Resultssupporting
confidence: 82%
“…In previous studies, we found that OA induced apoptosis of HCT116 cells. 23 Here, HCT116 cells were prestimulated with 50 μ M PA. The results of MTT assay and Ki67 staining showed that OA inhibited the growth of HCT116 cells with the IC50 value of 38.7 μ M under hypoxia ( Figures 3a and b ).…”
Section: Resultsmentioning
confidence: 99%
“…p53 is an important aging factor that controls cellular senescence [ 40 , 41 ]. p53 regulates mitochondrial functions [ 42 , 43 ] and redox homeostasis in part through the control of SOD2 expression [ 33 , 34 ]. p53 is an important tumor suppressor in human cancer and TP53 is estimated to be mutated in 30-50% of human liver cancer according to the cBioPortal ( http://www.cbioportal.org ).…”
Section: Discussionmentioning
confidence: 99%